Communities, Landscapes, and Interaction in Neolithic Greece - Sarris, Apostolos (International Monographs in Prehistory: Archaeological Ser, 2018)
Communities, Landscapes,and Interaction in NeolithicGreece -- Copyright -- Table of Contents -- List of Contributors -- List of Figures -- List of Tables -- Chapter 1. Communities, Landscapes, and Interaction -- Part I: Communities, Social Spaces, and Dimensions of Neolithic Lifeways (and Death) -- Chapter 2. The Transition from the Mesolithic to the Neolithic in a Circum-Aegean Perspective -- Chapter 3. Opening a New Frontier in the Study of Neolithic Settlement Patterns of Eastern Thessaly, Greece -- Chapter 4. A Road to Variation -- Chapter 5. An Investigation of Neolithic Settlement Pattern and Plant Exploitation at Dikili Tash -- Chapter 6. Koutroulou Magoula in Phthiotida, Central Greece -- Chapter 7. The Environment and Interactions of Neolithic Halai -- Chapter 8. Diros in Context -- Chapter 9. Visviki Magoula Revisited -- Chapter 10. Kouphovouno (Lakonia) -- Chapter 11. Pictures of Home -- Chapter 12. Community Interaction and (Intended) Land Use in Neolithic Greece -- Chapter 13. Fluid Landscapes, Bonded People? -- Part IΙ: Landscape Dynamics and Subsistence Strategies -- Chapter 14. Islands Out of the Mainstream -- Chapter 15. Cycladic or Mainland? -- Chapter 16. Human-Landscape Interaction in Neolithic Kephalonia, Western Greece -- Chapter 17. Submerged Neolithic Landscapes off Franchthi Cave -- Chapter 18. Humans, Animals, and the Landscape in Neolithic Koutroulou Magoula, Central Greece -- Chapter 19. Farming Strategies at Kouphovouno, Lakonia, in the MN-LN Periods -- Chapter 20. Animal Husbandry and the Use of Space in the Greek Sector of the Late Neolithic Settlement of Promachon-Topolnica -- Part ΙII: Interactions and MaterialPerspectives -- Chapter 21. Social Interaction in the Farming Communities of Neolithic Greece -- Chapter 22. Patterns in Contemporaneous Ceramic Traditions.